2021
DOI: 10.3390/vetsci8110259
|View full text |Cite
|
Sign up to set email alerts
|

Porcine Reproductive and Respiratory Syndrome Surveillance in breeding Herds and Nurseries Using Tongue Tips from Dead Animals

Abstract: The detection capacity of Porcine Reproductive and Respiratory Syndrome virus (PRRSV) in tongues from dead animals in breeding herds (stillborns and piglets dying during the lactating period) and nursery farms (naturally dead animals) for PRRSV surveillance was evaluated. The samples were selected if pairs of serum and tongues were available from 2018 to 2020. Serum (pools of five) and exudate from tongues (one bag) were analyzed by PRRSV RT-PCR. The agreement between the serum sample procedure versus tongues … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
11
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(12 citation statements)
references
References 21 publications
(35 reference statements)
1
11
0
Order By: Relevance
“…Interestingly, the average Ct value from tongue tips was numerically lower than the average Ct value from serum samples in newborns (<24 h). This finding agreed with Baliellas et al ( 13 ), and it might be explained by the fact that tongue tips were derived from dead animals, which were potentially more likely to harbor PRRSV. Additionally, PRRSV viremia can be detected 6 to 48 h post-infection ( 17 ), and PRRSV RNA-positive tongue tips from neonatal pigs were demonstrated in this study to be great indicators of PRRSV activity in the breeding herd and could be an alternative tool to umbilical cords ( 18 ), serum, and placenta to characterize vertical transmission in stillbirths.…”
Section: Discussionsupporting
confidence: 93%
See 4 more Smart Citations
“…Interestingly, the average Ct value from tongue tips was numerically lower than the average Ct value from serum samples in newborns (<24 h). This finding agreed with Baliellas et al ( 13 ), and it might be explained by the fact that tongue tips were derived from dead animals, which were potentially more likely to harbor PRRSV. Additionally, PRRSV viremia can be detected 6 to 48 h post-infection ( 17 ), and PRRSV RNA-positive tongue tips from neonatal pigs were demonstrated in this study to be great indicators of PRRSV activity in the breeding herd and could be an alternative tool to umbilical cords ( 18 ), serum, and placenta to characterize vertical transmission in stillbirths.…”
Section: Discussionsupporting
confidence: 93%
“…Baliellas et al ( 13 ) reported that the optimum number of tongue tips per bag was 30 to 100 to obtain enough exudate for PCR testing. However, in this study, tongue tips were collected by room and pig age group, with the number of tongues per bag limited by the number of daily dead pigs.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations